Characterization and stability studies of a novel liposomal cyclosporin A prepared using the supercritical fluid method: comparison with the modified conventional Bangham method - Karn, Pankaj Ranjan (Dove Medical Press, 2013)
A novel method to prepare cyclosporin A encapsulated liposomes was introduced using supercritical fluid of carbon dioxide (SCF-CO(2)) as an antisolvent. To investigate the strength of the newly developed SCF-CO(2) method compared with the modified conventional Bangham method, particle size, zeta potential, and polydispersity index (PDI) of both liposomal formulations were characterized and compared. In addition, entrapment efficiency (EE) and drug loading (DL) characteristics were analyzed by reversed-phase high-performance liquid chromatography. Significantly larger particle size and PDI were revealed from the conventional method, while EE (%) and DL (%) did not exhibit any significant differences. The SCF-CO(2) liposomes were found to be relatively smaller, multilamellar, and spherical with a smoother surface as determined by transmission electron microscopy. SCF-CO(2) liposomes showed no significant differences in their particle size and PDI after more than 3 months, whereas conventional liposomes exhibited significant changes in their particle size. The initial yield (%), EE (%), and DL (%) of SCF-CO(2) liposomes and conventional liposomes were 90.98 ± 2.94, 92.20 ± 1.36, 20.99 ± 0.84 and 90.72 ± 2.83, 90.24 ± 1.37, 20.47 ± 0.94, respectively, which changed after 14 weeks to 86.65 ± 0.30, 87.63 ± 0.72, 18.98 ± 0.22 and 75.04 ± 8.80, 84.59 ± 5.13, 15.94 ± 2.80, respectively. Therefore, the newly developed SCF-CO(2) method could be a better alternative compared with the conventional method and may provide a promising approach for large-scale production of liposomes.